A shipwreck in Fiji - Rao, Nilima (Soho Crime, 2025)
"A young Indian police sergeant investigates a bizarre chain of events when a purported sighting of Germans in 1915 Fiji turns deadly in this charming follow-up to A Disappearance in Fiji. Sergeant Akal Singh, an unwilling transplant to Fiji, is just starting to settle into his life in the capital city of Suva when he is sent to the neighboring island of Ovalau on a series of fool's errands. First: investigate strange reports of Germans, thousands of miles from the front of World War I. Second: chaperone two strong-willed European ladies, Mary and Katherine, on a sight-seeing tour. And third: supervise the only police officer currently on Ovalau, an eighteen-year-old constable with a penchant for hysterics. Accompanied by his friend Taviti (the nephew of a powerful chief), Akal sets off for what he thinks will be fairly straightforward tasks. Instead, they stumble upon a gruesome scene: the man who'd reported the Germans beaten to death in his own shop. Shortly after, the Germans (or are they Norwegians?) find themselves imprisoned in a local village for committing a taboo crime, and Katherine, the charming aspiring journalist, harbors an agenda of her own. Will Akal be able to keep her-and himself-out of trouble before anybody else gets killed? Nilima Rao's debut, A Disappearance in Fiji, was a critical darling and award-winner, ending up on multiple best-of-year roundups. This next installment in the Sergeant Akal Singh series has all the charm and sparkle of the first book, with even more fascinating historical insight into the realities of life on Fiji at the start of the twentieth century"--